Social Media and Employment – Students' vs. Employers' Perspective - Mirela Mabić; Dražena Gašpar; Lidija Lesko Bošnjak (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Recently, social media has become an integral part of different business activities. One of these activities is the recruitment and selection of employees. The paper presents the results of empirical research conducted among the students of the University of Mostar, Bosnia and Herzegovina (BH) and BH employers related to the use of social media in the process of recruitment and selection of new employees. The aim of the research is to find if there are similarities or/and differences in standpoints of students and employers concerning the use of social media in job finding and recruitment. The results show that most students and employers recognized social media as a valuable tool in the process of job finding, i.e., recruiting. However, both students and employers expressed reserve about data accuracy on social media. Students were resolute that their activities on social media should not affect their employment, while employers saw social media only as an additional tool in human resource management.
Keywords: O15; L86; J24; 330; social media; job-finding; recruitment; students; employers